Citizen schools A practical guide to education for citizenship and personal development - Alexander, Titus (Buckingham St., London Campaign for Learning, 2001)
Becoming a Citizenship School is a natural next step for schools wanting to motivate and equip young people for life in our complex society argues Titus Alexander in this practical guide. With photocopiable activities, extensive resource section and case studies showing how many schools are already making citizenship an every day experience for young people, the book is a must for those wanting to go beyond the citizenship curriculum in schools. Citizenship Schools is a practical guide to education for citizenship and personal development
Essential elements of a citizenship school -- Building a new learning constitution: the role of government -- What is citizenship education? -- Citizenship and the purpose of education -- The joy and power of learning -- Creating a culture of citizenship -- Learning freedom: the empowering classroom and curriculum -- Taking part: creating a learning democracy -- Building a new learning constitution: the role of government -- Materials, trainers, and organisations for learning citizenship.
Includes bibliographical references
Keywords: Civics -- Study and teaching; Citizenship -- Study and teaching